Believer's Bible commentary - MacDonald, William, 1917-2007; Farstad, Arthur L (Secunderabad G S Books, 2017)
Keyed to the New King James Version, with numerous photographs, maps and charts. MacDonald tackles controversial issues, taking a theologically conservative stand, yet presenting alternate views--
Introduction to the Old Testament. Introduction to the Pentateuch ; Introduction to the historical books ; Introduction to the poetical books ; Introduction to the Prophets -- The intertestamental period -- New Testament.
"A complete Bible commentary in one volume"--Cover.
Originally published in two separate volumes.
Includes bibliographical references.
Keywords: Bible -- Commentaries; Bible; One Volume commentary/ Bible; Commentaries